Экологические преимущества применения при шлифовании электроэрозионной правки алмазных кругов на металлических связках взамен электрохимической правки - Новиков, Федор Васильевич; Новиков, Григорий Васильевич; Дитиненко, Станислав Александрович; Полянский, Владимир Иванович (НТУ "ХПИ", 2016)
Обоснованы экологические преимущества применения электроэрозионной правки алмазных кругов на металлических связках взамен традиционно применяемой электрохимической правки при шлифовании металлических и неметаллических материалов повышенной твердости (твердые сплавы, износостойкие наплавки и покрытия, алмазы, керамики и т.д.) и описаны разработанные на этой основе технологические процессы шлифования. Показано, что применение электроэрозионной правки в отличие от электрохимической правки не требует использования вредных для здоровья рабочего электролитов, обработка производится с применением обычной технической воды. Даны практические рекомендации, обеспечивающие повышение производительности и снижение себестоимости обработки.

Substantiated environmental benefits of the use of EDM dressing of diamond wheels on metal bonds used to replace traditional electrochemical changes in grinding metallic and nonmetallic materials of high hardness (hard metals, wear-resistant surfacing and coating, diamonds, ceramics, etc.), and are described on this basis, developed processes grinding. It is shown that the use of electrical discharge changes unlike electrochemical changes do not require the use of harmful working electrolyte, the processing is performed using conventional industrial water. In particular as it relates to the operations of cut natural diamonds in diamonds, as a result of the establishment of the diamond wheel on a metal tray in conjunction with the electrolyte, the electrolyte comes splashing and contamination of workplace chemically active substances. Application of EDM dressing eliminates this phenomenon. It is also shown that the use of EDM dressing of diamond wheels metal bond eliminates from the process of natural diamond processing diamond wheels made electrogalvanic method, which is still less environmentally "clean" method in comparison with the electrochemical editing circle, as you have to use significant amounts of harmful health workers electrolytes. The Rabo those practical recommendations, providing improved performance and processing quality, cost reduction.
The environmental benefits of applying for grinding EDM dressing of diamond wheels on metal bonds instead of electrochemical changes
Keywords: искусственные алмазы; экологически безопасные технологии; электролиты; порошковая металлургия; труднообрабатываемые материалы; grinding; EDM dressing; electrochemical dressing; environmentally sound technologies; powder metallurgy